Cutaneous mucormycosis - Castrejón Pérez, Ana Daniela; Welsh Hernández, Esperanza C.; Miranda Maldonado, Ivett C.; Ocampo Candiani, Jorge; Welsh Lozano, Oliverio (2017)
Cutaneous mucormycosis is an emerging fungal infection caused by opportunistic fungi of the phylum Glomeromycota. It is frequent in poorly controlled diabetic patients and individuals with immunosuppression. It is usually acquired by direct inoculation through trauma. The clinical presentation is nonspecific, but an indurated plaque that rapidly evolves to necrosis is a common finding. Diagnosis should be confirmed by demonstration of the etiological agent and new molecular diagnostic tools have recently been described. It is an invasive life-threatening disease and in order to improve survival, a prompt diagnosis and multidisciplinary management should be provided. The treatment of choice is amphotericin B, but new azoles, such as posaconazole and isavuconazole, must be considered. Keywords: Mucormycosis; Mucorales; Mucor; Zygomycosis; Rhizopus